Nano‐ and Microscale Engineering of the Molybdenum Disulfide‐Based Catalysts for Syngas to Ethanol Conversion. Issue 8 (15th July 2014) - Konarova, Muxina; Tang, Fengqiu; Chen, Jiuling; Wang, Geoff; Rudolph, Victor; Beltramini, Jorge
Abstract Nickel‐promoted MoS2, unsupported catalysts and laponite‐supported alcohol synthesis catalysts were synthesised by using microemulsion (ME) and hydrothermal (HT) methods. Highly ordered sulfide slabs, consisting of up to seven layers, were visible in the TEM images of HT‐based NiMoS2 catalysts. In contrast, disordered sulfide layers were identified in ME‐based NiMoS2 catalysts. High catalytic activity was observed in ME‐based supported (laponite‐supported NiMoS2) and unsupported catalysts. After the CO hydrogenation reaction, the catalysts were characterised by X‐ray photoelectron spectroscopy and inductively coupled plasma–mass spectrometry elemental analyses, which detected a significant sulfur loss in ME‐based NiMoS2 catalysts and minor sulfur loss in HT‐based NiMoS2 catalysts. In addition to the large surface area (120 m2 g−1), disordered sulfide structure, and exposed active sites, ME‐based NiMoS2 catalysts demonstrated higher alcohol selectivity (61 mol %) than HT‐based NiMoS2 catalysts (15 mol %). Correlations between the catalyst morphology, surface active components, and alcohol selectivity are discussed herein.